2019
DOI: 10.1519/jpt.0000000000000167
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Equine-Assisted Therapy to Improve Balance, Functional Capacity, and Cognition in Older Adults With Alzheimer Disease

Abstract: These findings provide evidence of an association between EAT and improved balance and functional capacity in older adults with AD, with no significant impact on cognitive performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 42 publications
1
46
0
1
Order By: Relevance
“…Despite the accumulation of evidence that supports the benefits of AAI on symptoms of AD, which includes improving cognitive impairment, BPSD, and negative emotions (Kanamori et al, 2001;Bono et al, 2015;Menna et al, 2016;Borges de Araujo et al, 2019;Santaniello et al, 2020), the underlying neurological mechanisms of these benefits have not been identified yet. In particular, we speculated that increased emotional or social interaction through AAI plays an important role in relieving symptoms in patients with AD.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the accumulation of evidence that supports the benefits of AAI on symptoms of AD, which includes improving cognitive impairment, BPSD, and negative emotions (Kanamori et al, 2001;Bono et al, 2015;Menna et al, 2016;Borges de Araujo et al, 2019;Santaniello et al, 2020), the underlying neurological mechanisms of these benefits have not been identified yet. In particular, we speculated that increased emotional or social interaction through AAI plays an important role in relieving symptoms in patients with AD.…”
Section: Introductionmentioning
confidence: 99%
“…Equine-Assisted Therapy (EAT) is an effective way of improving many measures of physical health 12,13 . However, studies approaching the effects of EAT on the cardiovascular system are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…So far the studies carried out on Animal Assisted Interventions (AAI) have been mainly focused on the well-being of the patients. In general, these studies show a positive effect of equine assisted therapy in patients with cerebral palsy and other psychomotor disorders, with an improvement in global motor development [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Thus, studies carried out on equine assisted therapy show an improvement in balance, range of movements, postural control, functionality and motor control [ 4 , 6 , 8 , 9 , 10 ]; as well as an improvement in cognitive, sensory and emotional capacities [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, these studies show a positive effect of equine assisted therapy in patients with cerebral palsy and other psychomotor disorders, with an improvement in global motor development [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Thus, studies carried out on equine assisted therapy show an improvement in balance, range of movements, postural control, functionality and motor control [ 4 , 6 , 8 , 9 , 10 ]; as well as an improvement in cognitive, sensory and emotional capacities [ 3 , 5 ]. Some authors [ 11 ] determined that the functional improvements obtained in children with infantile cerebral palsy were, essentially, due to the movements the horse transmitted to the rider’s body, these impulses being three-dimensional, rhythmic and equivalent to the physiological pattern of human walking.…”
Section: Introductionmentioning
confidence: 99%